Efektifitas Senam Hamil Terhadap Nyeri Kram Kaki Ibu Hamil di Desa Bulurejo - Nuristy Brillian Ainindyahsari Winarna; Sholihin Sholihin; Filianingrum Ade Saputri (Jurnal Kesehatan Amanah, 2024)
Leg cramp pain, namely stiffness of the calf and leg muscles, occurs in the second and third trimesters. The impact of leg cramps is that the legs get tired quickly and tingling if left untreated, the veins can burst and cause blood clots. The solution to overcome the discomfort of leg cramps is by doing pregnancy exercises. Pregnancy exercise Muscle relaxation exercises for the health and fitness of pregnant women. This study aims to analyze the effectiveness of pregnancy exercise on leg cramp pain in pregnant women. This type of quantitative research uses a pre-experimental design using a one group pretest – posttest design approach. The total sample was 30 people according to the inclusion criteria, namely primigravida and multigravida pregnant women aged more than 13 weeks to 35 weeks, pregnant women who experienced leg cramps, pregnant women who were willing to be respondents. The research technique uses total sampling. The instrument used in the research was the Hayward pain scale. Pregnancy exercise is carried out 12 meetings per month (1 week 3 times) using the Pregnancy Exercise SOP to relieve leg cramp pain. Data analysis used the Wilcoxon test because the data was not normally distributed. The results of the study showed that all respondents before being given pregnancy exercises experienced moderate pain (scale 4 - 6) and after doing pregnancy exercises it decreased to mild pain (scale 1 - 3). The results of the statistical output test of nonparametric statistical tests using the Wilcoxon test with SPSS for pain before and after the intervention obtained a p value <0.001, meaning that there is effectiveness of pregnancy exercise on leg cramp pain in pregnant women. Every pregnant woman who regularly does pregnancy exercises can reduce the pain of leg cramps and it is hoped that midwives can work together to increase education regarding leg cramp pain and the benefits of pregnancy exercises, so that pregnant women have the awareness to do pregnancy exercises.